Dioscin Reduces Vascular Damage in the Retina of db/db Mice by Inhibiting the VEGFA Signaling Pathway - Jun Wang; Guang Yan Yang; Hong Yan Sun; Ting Meng; Chu Chu Cheng; Hui Pan Zhao; Xiao Ling Luo; Ming Ming Yang (Frontiers Media S.A., 2022)
Diabetic retinopathy (DR) is a complication of diabetes that has a serious impact on the quality of life of patients. VEGFA is necessary in the physiological state to maintain endothelial activity and physical properties of blood vessels. VEGFA plays an important role in the promotion of neovascularization; therefore, inhibition of VEGFA can degrade the structure of blood vessels and reduce neovascularization. In the present study, HERB, a high-throughput experimental and reference-oriented database of herbal medicines, was used for compound mining targeting VEGFA. The compounds most likely to interact with VEGFA were screened by molecular docking. Next, the compounds were used to verify whether it could inhibit the activity of the VEGF signaling pathway in vitro and neovascularization in vivo. In vitro, we found that dioscin could inhibit the activation of the VEGFA-VEGFR2 signaling pathway and cell proliferation of human retinal microvascular endothelial cells in a high-glucose (HG) environment. A more important dioscin intervention inhibits the expression of pro-angiogenic factors in the retinas of db/db mice. In conclusion, our study indicates that dioscin reduces the vascular damage and the expression of pro-angiogenic factors in the retina of db/db mice and implies an important and potential application of dioscin for treatment of DR in clinics.